Molecular profiling and detection methods of microRNA in cancer research - Imilia, Ismail; Nurul-Syakima, Ab Mutalib; Ser, Hooi-Leng (2020)
A large portion of human genome was believed to be “useless” and termed as “junk DNA” in the past, given that these sequences did not have any protein coding role. However, with more researchers dwelling into the world of these mysterious genetic codes, a group of non-protein coding RNA (ncRNA) known as microRNAs (miRNAs) is now being recognized to play important roles than they were thought to be. In truth, the first discovery of miRNA was in a simple organism -nematode (scientific name: Caenorhabditis elegans), whereby a mutant displayed aberrant morphological changes. Years after that, researchers then realized that these miRNAs are actually important regulatory molecules — controlling cell division signaling, apoptosis and so on. In fact, the unusual expression of miRNAs has also been associated in etiology of various cancers. Acting like a “double-edge” sword, miRNAs can control and/or act as tumor suppressor genes and oncogenes, thus any unwanted alterations in their expression would bring upon disastrous effects on the host. Therefore, the current review aims to summarize the molecular detection tools that are available for miRNA profiling in cancer research.